Clinical and economic benefits of using sonidegib in the 1-line therapy of patients with locally advanced basal cell carcinoma - O. I. Ivakhnenko; V. V. Ryazhenov; M. Yu. Frolov; V. A. Rogov (Фармация и фармакология (Пятигорск), 2025)
One of the key factors in ensuring the availability of modern treatments and choosing the optimal therapy for patients is the clinical and economic characteristics of new medical technologies.The aim: to assess the clinical and economic feasibility of using sonidegib in widespread clinical practice.Materials and methods. General scientific research methods were used as a methodological basis. A "decision tree" model was developed to conduct a clinical and economic assessment. The clinical and economic assessment of the use of sonidegib was carried out from the perspective of the healthcare system of the Russian Federation: the costs of systemic drug therapy for the 1-line of patients with locally advanced basal cell carcinoma (BCC) were taken into account.Results. A comparative analysis of efficacy based on the progression-free survival (PFS) criterion revealed the advantage of sonidegib over vismodegib: the odds ratio (OR) of disease progression in patients with locally advanced BCC 12 months after the start of therapy was 0.27778 (95% CI 0.125–0.618; p=0.0017; Z=3.1423). The reduction in the risk of progression when using sonidegib compared to vismodegib was 59.1% (OR= 0.409; 95% CI 0.229–0.732, p=0.0026, Z=3.013). The results of testing the hypothesis about the equality of the proportion of patients with locally advanced BCC without disease progression 12 months after the start of therapy also confirmed the presence of statistically significant differences in efficacy between the two treatments in favor of sonidegib (χ2=9.2007, df=1, p=0.002419, 95% CI 0.09312–0.432132). The use of sonidegib in the 1-line of therapy, 2.53 million rubles per year will be required per 1 patient, which is 10.86% lower than the use of vismodegib, and corresponds to an absolute saving of 308.55 thousand rubles. The "cost-effectiveness" indicator (CER) for sonidegib was 114,627 rubles versus 220,295 rubles for vismodegib. The incremental cost-effectiveness ratio (ICER) is 175,050 rubles per additional month of PFS. Sensitivity analysis showed the stability of the results when changing key parameters.Conclusion. Based on the results of the study, the hypothesis about the clinical and economic benefits of sonidegib in the treatment of locally advanced BCC was confirmed, and data were obtained on the clinical and economic feasibility of using sonidegib in widespread clinical practice.